A separate set of guidelines for screen time used for recreation versus education—The need of hour for a child’s education in post-COVID era - Neha Thakur Rai; Arvind Kumar Singh; Devesh Kumar Shukla; Narendra Rai (Journal of Family Medicine and Primary Care)
Background: The duration of time spent on electronic or digital media is defined as screen time. Digital media expansion and COVID-19 pandemic have made children more inclined towards screen time both as a necessity and as a habit. Materials and Methods: A cross-sectional study on children, aged two to five years, was conducted for one year (2021–2022). Parents were asked to self-fill a designed questionnaire. Impacts on physical and mental health of children and the necessity of screen time were assessed by paediatrician and psychologist. Results: A total of 650 children (354 boys and 296 girls) participated in the study. The mean screen time of parents was 6.4 hours. ± 2.32 and children were 4.95 ± 2.34 hours. 98.75% of children had screen time more than that recommended for age. Children were exposed to screen time at the tender age of three months. COVID-19 increased screen time by more than 1 hour in 92% of children. The most common gadget used was mobile phones (n = 628, 96.6%), followed by television (n = 511, 78.7%). Screen time had a negligible effect (P = 0.611) on the nutritional status of children. However, it had a significant effect on psychosocial behaviour (P = 0.05), ophthalmologic problems (P = 0.03), sleep cycle (P = 0.00), and academic performance (P = 0.002). Fathers’ occupation (P = 0.00), age of onset of screen time (P = 0.00), and parental setting of time limit for screen time (P = 0.009) were significant contributors to increase screen time. Conclusion: Findings suggested poor awareness among parents/caregivers regarding the negative impact of high screen time on children. Parents felt that screen time was a part of a normal day-to-day life and was important, particularly in post-COVID era when education was shifted from schools to laptops.